Proceedings of the 2nd International Living Usability Lab Workshop on AAL Latest Solutions, Trends and Applications, AAL 2012, in Conjunction with BIOSTEC 2012 - Dias, J.; Teixeira, A.; António Teixeira; Teixeira, A; Daniela Braga (2012)
Foreword: Welcome to the Second International Living Usability Lab Workshop on AAL Latest Solutions, Trends and Applications (AAL 2012), organized by Institute for Systems and Technologies of International Control, in cooperation with the QREN 7900 Living Usability Lab Consortium led by Microsoft Portugal, with PLUX, IEETA, Engineering Faculty of University of Porto, INESC Porto, Micro IO and University of Aveiro as partners. Following the success of last year’s edition, held in Rome, the organizing committee decided to continue this event under the scope of BIOSTEC 2012 (5th International Joint Conference on Biomedical Engineering Systems and Technologies), held this year in Vilamoura, Algarve, Portugal, from 1st -4th February 2012. The purpose of the AAL 2012 workshop is to present the latest scientific results in the growing and promising field of Ambient Assisted Living and to provide a forum for discussing the achievements reached so far, in the context of the collaborative R&D project Living Usability Lab (LUL) for next generation networks, as well as other initiatives. Natural and multimodal user interfaces, such as speech, gesture and touch, interfacing technological solutions and services, such as remote elderly care support and telehealth, ambient intelligence, pervasive environmental monitoring, indoor localization for safety and security, audio-visual communication and social media, are just a few examples of such Ambient Assisted Living technologies and services that promote independent living and active ageing. Demographic ageing is probably the greatest achievement of mankind. As such, senior population is growing faster and consequently physical or mental impairments, disabilities and chronic illnesses are arising. This situation has an enormous economic and social impact in a number of areas, and so the world is coming across a challenge: to take advantage of the suitable natural interfaces and the possibilities offered by next generation networks and to introduce technological solutions that can improve the elderly health via remote means, while facilitating their daily life, fighting isolation and exclusion, increasing their pro-activity, work capacity, safety and autonomy. This way, AAL 2012 is a forum for debating all these ideas and to present technological advances, bearing in mind the human factor, that respond to this global challenge. AAL 2012 workshop has received 12 paper submissions. After a careful and blind peer review, five submissions were accepted as full papers and five submissions as short papers. Long papers topics cover social inclusion, multimodal HCI, usability evaluation for communication services targeting mobility impaired users, mobility in domestic environments, infrastructures and services for home telerehabilitation, and Services and solutions using robotics for elderly care. Short papers reflect work-in-progress or position papers addressing topics such as representation of medical data in AAL solutions, ECG signals acquisition, positioning and monitoring using wireless platforms, state of the art in the AAL area in general and, particularly, in Portugal. The program for this workshop required the dedicated effort of many people. Firstly, we must thank the authors, whose research and development efforts, willing to advance science and technology for the benefit of the AAL field, are recorded here. Secondly, we thank the members of the program committee and the additional reviewers for their diligence and expert reviewing. Finally, we send special thanks to all members of the INSTICC, especially Vera Coelho of the conference secretariat, whose collaboration was instrumental for the success of this workshop. We wish you all an exciting conference and an unforgettable stay in the warm and cosmopolitan village of Vilamoura, in Algarve, Portugal. Proceedings of the 2nd International Living Usability Lab Workshop on AAL Latest Solutions, Trends and Applications February 1-4, 2012, in Vilamoura, Algarve, Portugal